KETERWAKILAN PEREMPUAN PADA PEMILIHAN BADAN PERMUSYAWARATAN DESA SEBAGAI UPAYA PARTISIPASI DALAM PEMBANGUNAN DESA - Ndruru, Meniwati (LPPM Universitas Nias Raya, 2024)
The institution that carries out government functions in the field of drafting and enacting Village regulations is the Village Consultative Body which is tasked with accommodating community aspirations in the context of preparing village income and expenditure budget programs and monitoring the performance of village government. Women's representation means participating in village development, both in the fields of government and in the fields of politics and education. Participation in village development is an effort to build and develop a particular village. In accordance with Article 5 Number 110 of the Indonesian State Protection Law of 2016. Regarding the Village Consultative Body, it is determined that a woman is elected to become a member of the BPD by calling members of the BPD in accordance with women's representation as intended in article 6 letter b. The type of research used is sociological legal research, namely an approach carried out directly by examining relevant legal provisions and social realities. Primary and secondary data collected through interviews were used in the data collection process. A deductive approach is used in the analysis of observation data and documentation investigations, resulting in descriptive results. Based on research findings and discussions, it can be concluded that women's representation in the election of the Village Consultative Body (BPD) of Orahili Village still does not meet the requirements for filling in as members of the BPD. This is because women are still not involved in managing BPD members, not because they are limited, but because no woman has expressed a desire to run for office. Therefore, the author recommends socialization or community education that discusses women's representation in politics and gvernment, gender equality, and the importance and role of women in village government.